Unidades de conservação do Amapá: injustiça ambiental em pele de preservação da natureza? - Maria Emília Oliveira Chaves (2018)
This research presents an academic and vertical view of the present situation of Conservation Units located in the territorial limits of the State of Amapá, whether federal, state or municipal, since such protected areas occupy more than 60% of the total area of Amapá, a percentage that rises to more than 70.2%, if added to the Indigenous Lands. This situation generates impacts of land, social, economic and environmental order of the region, creating a sui generis situation of these demarcations (in quantity and territorial extension) of Amapa in order to attend to national and / or international interests of preservation of nature to the present and future generations, instituted without the provision of information and guaranteeing popular participation, especially of the surrounding communities and residents in those places, and even though the Public Power has not been efficient in the management of these UC. In view of the theoretical current of Environmental Justice, which advocates that the costs of environmental degradation and economic growth should not be supported in disproportionate plots by the economically and socially disadvantaged populations, there was evidence of a causal link between the creation and management scenario of the PA in Amapá and the existence of Environmental Injustice in the face of the negative repercussions imposed on the population that can cause economic stagnation and violence in these localities to where these populations are displaced. The effectiveness and efficacy of society's engagement have historically revealed the assimilation of the amapaenses to the ideology of the processes of creation of the UC, manifested from the colonial period, through the creation of the Federal Territory of Amapá, when blacks had to move from their habitat to give way to the headquarters of the Janarista Government, following with this lack of participation and play of account that adequate means of participation of the local community have been provided that resents the environmental partition and injustice caused by the extension of the UC. The central issue of concern of this work concerns the aspects that concern sustainability, regarding the healthy quality of life. In this step, the concern that refers to the space that remains for human occupation of the future generations of people of the State of Amapá in front of the UC, as well as what territorial designs will be realized in front of the population growth without macularising the UC and without this environmental injustice neither harming the UC nor harming the right to the city of present and future generations, especially because the population of the State of Amapá is already experiencing this process of emparedamento, while recognizing a third phase of federalization (Colonial Period, creation of the Federal Territory of Amapá and the creation of UC of Federal jurisdiction). In view of this, the research analyzes the panorama of the state of Amapá (historical, territorial extension, management and influence in the local reality) to verify the presence or not of elements of Environmental Injustice. The methodological framework covered the process of creating UC, the participation of the local community, and the management mechanisms of such UC in a collate with elements of citizenship and sovereignty, seeking to understand the relationships and repercussions in the local context, taking into account the empowerment of UC to the detriment of the empowerment of populations. Bibliographical and electronic research was carried out in books, scientific articles, as well as the analysis of reports of external control bodies and pertinent federal, state and municipal regulations, and other data about Amapá UC, contained in databases of management bodies. It presents as hypothesis the possibility that the current conjuncture of the Amapá PA and the resulting territorial restriction, produce environmental injustice, with negative impacts to the population of the State, instead of resulting in an efficient policy of conservation and sustainable use of natural resources.